Language identity and cultural memory in borderland areas. A survey-based research with aged respondents (seniors) - Bonacchi, Silvia; Wicherkiewicz, Tomasz; Mela, Mariusz (Investigationes Linguisticae, 2019)
The article presents methodological and practical experiences of an inter-university research project “Language of boundaries – Boundaries of language. Paralinguistic aspects of intercultural communication”, one of project tasks being conducting interviews with Polish and German senior respondents. The project aims were, among others, to investigate linguistic and cultural awareness, the sense of proximity/alienness with the culture and the others in the transborder area and the processes of mutual accommodation. In this context, senior respondents are a particularly precious target group in language contact studies as they are witnesses of linguistic identity and cultural memory. The interviews took place in the Polish-German border region of Frankfurt/Oder and Słubice. The respondents were asked questions included in a questionnaire that was especially prepared for the purpose. The questions included among other things questions about the respondents’ origins, professional life, education, daily habits, languages spoken by them, attitudes towards the other cultural group. The authors have not only presented theoretical basics of transborder studies, accommodation processes and age studies, but they have also given practical tips on what should be considered when doing interviews with the elderly. The article includes a summary of the answers given by the two groups of the respondents. With the article, the authors intend to contribute methodologically to future socio- and gerontolinguistic studies. Badania zrealizowano w ramach projektu Język pogranicza – pogranicze języka. Parajęzykowe aspekty komunikacji międzykulturowej (UMO: Nr 0106/NPRH3/H12/82/2014) finansowanego przez Narodowy Program Rozwoju Humanistyki.